Foreign enterprise in Nigeria : laws and policies - Proehl, Paul O. (Chapel Hill : University of North Carolina Press, 1965)
This study forms part of a series of similar works which examine the legal climate for foreign investment in Asia, Africa and America. It is the first work of its type to deal with the laws of an African state with this purpose. Some of the topics covered are of an introductory Nigerian law) or deal with peripheral matters ( the Western region constitutional crisis of 1962 to 1963). But the remaining chapters range widely and helpfully over Nigerian law, statutory, Islamic and customary in its economic context. Entrepreneurship, labour laws, tax laws and land tenure, credit transactions, and Nigerianization policies with are the main fields so dealt with.
Includes index
Bibliographical references included in "Notes" (p. [197]-238)
usc 05/06/18
Loans
Keywords: Investments, Foreign; Nigeria